Feature & magazine writing action, angle, and anecdotes - Sumner, David E. 1946-; Miller, Holly G.; Sumner, David E. 1946- (Chichester, West Sussex, United Kingdom Wiley-Blackwell, 2013)
"Updated with fresh facts, examples and illustrations, along with two new chapters on digital media and blogs this third edition continues to be the authoritative and essential guide to writing engaging and marketable feature stories. Covers everything from finding original ideas and angles to locating expert sources Expanded edition with new chapters on storytelling for digital media and building a story blog Captivating style exemplifies the authors' expert guidance Authors combines academic authority with professional know-how Comprehensive coverage of all the angles, including marketing written work and finding jobs in the publishing industry Essential reading for anyone wishing to become a strong feature writer "--Provided by publisher.
What makes a story interesting? -- How to find an original idea -- Strong angles and focused ideas -- Digging deep for original stories -- Talking pointers : how to conduct great interviews -- To market, to market : shopping your words around -- Pitch-perfect query letters -- Where to begin : the first 100 words -- Action, brevity, and style -- Anecdotes : mining for gold -- Briefs : shortcuts to publication -- Profiles : slices of life -- Writing nonfiction narratives -- Eliminating the ho-hum from the how-to -- Making a timely calendar connection -- Writing about trends and issues -- Building a story blog -- Long-form digital storytelling -- Advancing beyond the slush pile -- Before you hit the "send" button : a checklist -- Careers in magazine publishing.
Includes bibliographical references and index.
Keywords: Feature writing; Journalism -- Authorship